Code Switching in Tetun Songs: The Way to Teach Language - I Made Dwi Kardiasa; I Nyoman Udayana; I Gusti Agung Istri Aryani (Indonesian Journal of EFL and Linguistics, 2023)
Nowadays, the use of language can be done through daily life conversations and in the form of works, one of which is a song. In connection with the function of language in social science, sociolinguistics was born, one of which is about code-switching. This research involves six popular songs from Timor Leste that use three language variations, namely Tetun, Indonesian, and English. As a result, three types of code-switching were found: tag switching, intra-sentential switching, and inter-sentential switching. From here, there are three functions of code-switching in these songs including proving that Tetun can be comparable to other languages, code-switching can be used to discuss certain topics, and finally, this phenomenon is also effective to show certain characteristics. The function of code-switching itself is also related to the language learning process for learners.